Ancient weapons of Oman. - Clarizia, Vincenzo, (Archaeological heritage of Oman ;, 2022)
This text presents a detailed overview of the firearms used in Oman over the last four centuries. Portable firearms, rifles and cannons are all discussed in detail with supporting illustrations. The weapons described in this book are mostly from the National Museum Oman and Bait al Zubair Museum in Muscat.